Strategic marketing channel management - Bowersox, Donald J.; Cooper, M. Bixby (New York : McGraw-Hill, 1992)
Business
Keywords: Marketing channel; Manufacturing; Strategic marketing; Marketing design; Logistics design; Planning; Negotiation; Channel management